RACISM REFLECTED IN MAYA ANGELOU’S POEM - Ria Resky Hardianti (Universitas Sembilanbelas November Kolaka, 2016)
The major problem of this research is racism reflected in Maya Angelou’s poems. The aim of this research is to find out how racism reflected in Maya Angelou’s poems. This research focuses in Maya Angelou’s poems especially about racism. The type of the research is qualitative research. The method of data collection is document analysis, and the technique of data collection is note taking, while the technique of data analysis is descriptive analysis in which the researcher interprets the text and the content of the poem. This research uses two data sources, namely primary and secondary data source. The primary data source of the study is Maya Angelou’s poem itself, from the collection of Maya Angelou published in 1994. The secondary data sources are Biography of the author Maya Angelou, websites in the internet about Maya Angelou, and other resources which support to analyze. Based on the sociological approach, the researcher concludes that Maya Angelou’s poems reflected racism based on the poem text and the expression in the poem. Maya Angelou’s poem also indicates types of racism such as slavery and discrimination. The last conclusion is Maya Angelou choose racism as the important issue in her poems because she is an African-American poet and activist